2006
DOI: 10.1088/0953-4075/39/5/r01
|View full text |Cite
|
Sign up to set email alerts
|

Open shells and multi-electron interactions: core level photoionization of the 3d metal atoms

Abstract: This review covers the outer core level photoionization of the free 3d metal atoms from Sc to Cu. The experimental 3p, 3s and 2p photoemission and photoabsorption spectra are discussed. A comparison emphasizes common features and distinct differences. The interpretation of the data based on ab initio calculations reveals the influence of multi-electron interactions in the 3d metal atoms. We focus on the fundamental effects and main interactions which govern the electronic structure of these open shell atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
114
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 207 publications
(420 reference statements)
8
114
1
Order By: Relevance
“…, Mn 2? and Mn(0) valence states, respectively [12][13][14][15]. As expected, two additional satellite peaks situated at around 660 and 649 eV were also observed [16][17][18].…”
Section: Resultssupporting
confidence: 56%
“…, Mn 2? and Mn(0) valence states, respectively [12][13][14][15]. As expected, two additional satellite peaks situated at around 660 and 649 eV were also observed [16][17][18].…”
Section: Resultssupporting
confidence: 56%
“…The highest-order harmonics have an increased electronic sensitivity since they are located at the onset of the vanadium M-edge [7].…”
Section: Resultsmentioning
confidence: 99%
“…The studies of the photoionization spectra of cadmium ions have also shown the presence of analogous strong ionic transitions. 12, 13 We did not find in literature the data on the oscillator strengths of the ionic transitions of cadmium in the spectral range of harmonic cutoff for the first plateau. Nevertheless, the above observations and assumptions allow us to suppose a decisive role of the spectral characteristics of ions in the formation of the optimal conditions when free electrons can be compensated for by the closeness of the next set of harmonics to the ionic transitions possessing strong oscillator strengths.…”
mentioning
confidence: 76%